A Local Wisdom E-module Ulur-Ulur for Promoting Geographic Literacy and Disaster Preparedness in Tulungagung Regency - Fahmi Adi Kusuma; Alfi Kurnia; Nilam Nur Hayati; Purwanto (Future Space: Studies in Geo-Education, 2025)
Teaching materials play a pivotal role in supporting effective learning, yet the integration of region-specific local wisdom into geography instruction remains limited. This study aims to develop a digital geography e-module grounded in the Ulur-Ulur tradition, a form of local wisdom in Tulungagung Regency, to enhance student understanding of drought mitigation and adaptation. Employing a research and development (R&D) approach, the study adopts the ADDIE instructional design model to guide the systematic development process. The participants included Grade XI social science students at SMAN 1 Gondang, with data collected through expert validation instruments and student response questionnaires. Data were analyzed using descriptive statistical techniques based on percentage scores. Validation results demonstrate strong feasibility: material validation achieved a score of 75% (feasible), teaching material design scored 90% (very feasible), and language validation attained 100% (very feasible). Student responses indicated a high level of acceptance and usability, with an overall feasibility score of 86%. These findings suggest that the Ulur-Ulur e-module is a contextually relevant, pedagogically sound, and practically feasible resource for integrating local knowledge into geography education. Its application not only enhances students’ cognitive engagement with disaster-related content but also promotes the development of place-based environmental awareness and adaptive capacity.